Enterprise Architecture Design for Non-Container Terminal Services: A Case Study of PT Pelindo Multi Terminal (SPMT) - I Putu Ega Septa; Betty Purwandari; Riri Satria; Raden Trimanadi; Raden Trimanadi (Dinasti Research, 2026)
Enterprise Architecture (EA) is a framework used to align business strategy with information technology in an integrated manner. However, in non-container terminal operations, the implementation of Information Systems/Information Technology (IS/IT) is still fragmented and has not been supported by a standardized enterprise architecture, making it difficult to achieve integration and optimize business processes. To support the standardization and digitalization of non-container terminal operations, EA design is required so that the development of information systems and technology can be carried out in a structured manner and aligned with business needs. This study aims to develop an EA design as a guideline for the development of Information Systems/Information Technology (IS/IT) in non-container terminal service companies, covering loading, unloading, receiving, and delivery processes. This research uses a qualitative method through interviews and document analysis. Thematic analysis of interview transcripts and documents is conducted to identify operational needs and existing system issues. The EA design is developed using the TOGAF 10 ADM framework, starting from the Business Architecture phase to the Technology Architecture phase. The results of this study are in the form of a business, data, application, and technology architecture blueprint that supports standardization, integration, and automation of operational processes through the implementation of systems such as SCADA, the development of PTOS-M, Warehouse Management System (WMS), and the utilization of the Internet of Things (IoT). The proposed architecture is expected to improve operational efficiency, system integration, and service quality in non-container terminal operations. This design is also expected to serve as a reference for IS/IT standardization and integration, as well as to contribute to the development of EA in the context of non-container terminals. Specifically, this architecture model uniquely integrates Information Technology (IT) and Operational Technology (OT) to enable real-time operational visibility and terminal automation, while incorporating security measures across both IT and OT layers.